2019
DOI: 10.1136/bmjopen-2018-026888
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Xpert CT/NG and OSOM Trichomonas Rapid assays for point-of-care STI testing among young women in South Africa: a cross-sectional study

Abstract: ObjectivesSyndromic management of sexually transmitted infections (STIs) omits asymptomatic infections, particularly among women. Accurate point-of-care assays may improve STI care in low- and middle-income countries (LMICs). We aimed to evaluate the diagnostic performance of the XpertChlamydia trachomatis/Neisseria gonorrhoeae(CT/NG) and OSOMTrichomonas vaginalis(TV) Test as part of a STI care model for young women in South Africa.DesignDiagnostic evaluation conducted as part of a prospective cohort study (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…10 Still, studies done in these settings have shown that the use of NAAT-based POC tests is acceptable and feasible, but additional costeffectiveness studies will be essential to justify the investment by health systems. [28][29][30][31] Cost-effectiveness studies in high-income settings have demonstrated that the tests can be cost-effective in different testing scenarios. 18,51 Ensuring adherence to the ASSURED criteria is one way to maximize the impact of new POC tests.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Still, studies done in these settings have shown that the use of NAAT-based POC tests is acceptable and feasible, but additional costeffectiveness studies will be essential to justify the investment by health systems. [28][29][30][31] Cost-effectiveness studies in high-income settings have demonstrated that the tests can be cost-effective in different testing scenarios. 18,51 Ensuring adherence to the ASSURED criteria is one way to maximize the impact of new POC tests.…”
Section: Resultsmentioning
confidence: 99%
“…29 Another study in South Africa demonstrated how the use of the assay could improve same-day treatment, facilitate expedited partner therapy, and reduce reinfection at 6 months. 30 A recent study in Rwanda established that the assay could be used to provide targeting screening to improve the WHO's syndromic treatment approach and resulted in a reduction in overtreatment of STIs. 31 The binx health io CT/NG Assay (binx health, Inc) is a rapid qualitative PCR-based diagnostic system that consists of a small, benchtop, fully integrated instrument that uses single-use, assay-specific cartridges.…”
Section: Naat-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 The study included a cohort of young, non-pregnant, HIV-uninfected women attending the Prince Cyril Zulu Communicable Diseases Centre for sexual and reproductive services in Durban, South Africa. 17 Women were excluded from the study if they reported the use of antibiotics or HSV treatments within the past 7 days or had engaged in any form of sex work. A total of 251 enrolled women consenting to genital specimen collection were included in this secondary analysis of baseline data.…”
Section: Methodsmentioning
confidence: 99%
“…Protected by copyright. 17 Women were excluded from the study if they reported the use of antibiotics or HSV treatments within the past 7 days or had engaged in any form of sex work. A total of 251 enrolled women consenting to genital specimen collection were included in this secondary analysis of baseline data.…”
Section: Participants and Specimen Collectionmentioning
confidence: 99%